Global survey of the diagnostic evaluation and management of cryptogenic ischemic stroke. Issue 7 (18th May 2015) - Giruparajah, Mohana; Bosch, Jackie; Vanassche, Thomas; Mattina, Katie; Connolly, Stuart J.; Pater, Calin; Hart, Robert G.
<x xml:space="preserve">Abstract</x> Background About 25% of ischemic strokes are categorized as cryptogenic (i.e. of unknown cause), but few data exist about the extent of diagnostic testing or treatment. We undertook an international survey to characterize current diagnostic evaluation and antithrombotic management of patients with cryptogenic ischemic stroke in 2014. Aims/Hypothesis To determine the type of diagnostic evaluation undertaken for cryptogenic ischemic stroke and antithrombotic management and to compare across global regions. Methods An 18‐question online survey was sent to 995 physicians involved in stroke care in 61 countries. Countries were separated into World Bank global regions and income groups. Diagnostic tests were considered routine if performed in >75% of patients at a center. Results Three hundred one completed surveys were received from 48 countries (response rate ∼30%). The majority (82%) of hospitals were from high‐income countries and mainly from Europe and Central Asia (56%) and North America (19%). For ischemic stroke patients, magnetic resonance imaging is routinely obtained at 36% of hospitals (highest in North America, 58%). Among cryptogenic stroke patients, transesophageal echocardiography is routinely performed in 17% of hospitals. More than 24 hour cardiac rhythm monitoring is done routinely at relatively few (17%) hospitals (highest in North America, 33%). Intracranial arterial imaging is done routinely at 70% of hospitals, with no significant regional differences. Antiplatelet therapies are routinely prescribed for secondary prevention at 94% of hospitals. Conclusions Based on self‐selected respondents from a large number of international stroke centers, transesophageal echocardiography and prolonged (>24 h) cardiac rhythm monitoring are not routinely performed in cryptogenic stroke patients, even in high‐income countries. Antiplatelet therapy is the global standard for secondary prevention of cryptogenic stroke.